Sinusoidal movement of a grating across the monkey's fingerpad: temporal patterns of afferent fiber responses - Morley, JW (J Neurosci, 1987)
Responses were recorded from cutaneous afferents innervating mechanoreceptors in the monkey's fingerpad, while gratings of alternating grooves and ridges were moved sinusoidally across their receptive fields. The gratings were specified by their spatial period and the movement by its peak speed: together these determined the peak temporal frequency at which grating ridges passed over the receptive field. During the central 42 degrees of each half cycle of movement, the speed and thus the temporal frequency of the grating ridges remained constant to within 6.6% of their peak values. In this region the responses of all afferents were phase-locked to the temporal sequence of grating ridges. The number of impulses elicited by each grating ridge was a function of the stimulus variables. For all 3 afferent classes--namely, slowly adapting afferents (SAs), rapidly adapting afferents (RAs), and Pacinian afferents (PCs)--the number of impulses per grating ridge increased as the spatial period of the grating increased (while the peak speed of movement was held constant). Similarly, for all 3 classes, the number of impulses per ridge decreased as the peak speed of movement increased (while the spatial period of the grating remained constant). When the peak temporal frequency of the grating ridges was held constant, for SAs and RAs the number of impulses per ridge increased with an increase in the spatial period of the grating and thus with an increase in the peak speed. These phase-locked responses provided information about the peak temporal frequency of the grating ridges independent of the grating spatial period and of the peak speed of movement. The shape of the response profile during a half cycle of movement was different for different afferents. Many of the RA response profiles were close to sinusoidal. The SA and PC profiles tended to have reduced peaks or raised troughs, resulting in flatter profiles. Other departures from sinusoidal profiles were also seen.